Antidiabetic potential of Phaleria macrocarpa fruit liquid CO₂ extract: Bioactivity, cytotoxicity, phytochemicals and molecular targets - Md Abdur Rashid Mia; Qamar Uddin Ahmed; Sahena Ferdosh; Md Shahidul Islam; Mohammad Shahzad Samdani; Md Zaidul Islam Sarker (Phytomedicine Plus)
Type 2 diabetes is a chronic metabolic disorder marked by impaired insulin utilization and elevated blood glucose levels. Synthetic drugs often fall short in fully regulating glucose and can cause deleterious side effects during the treatment of diabetes. In contrast, medicinal plants are believed to manage diabetes effectively and alleviate its symptoms. Phaleria macrocarpa fruit has been traditionally used in Southeast Asia to treat various diseases, including diabetes mellitus. This research aims to evaluate the antidiabetic effects of P. macrocarpa fruit extract, identify its antidiabetic compounds, and elucidate their mechanisms of action. The fruit flesh of P. macrocarpa was extracted using liquid CO2 and ethanol under subcritical conditions to obtain a liquid CO2 extract (LCE), while a heat reflux extract (HRE) was prepared using ethanol. Both LCE and HRE were assessed for total phenolic, flavonoid contents, α-glucosidase inhibition and cytotoxicity effects. The most bioactive fraction, LCE, was tested in a mice model. The in vivo antidiabetic effect of LCE was evaluated biochemically and histologically. LCE was analysed by LCMS-MS, and the identified compounds were evaluated for ADME and toxicity properties, followed by QSAR and molecular docking to confirm antidiabetic properties. LCE showed higher total phenolic (100.9 ± 3.02 mg GAE/g), flavonoid (92.26 ± 1.21 mg QE/g) contents, and α-glucosidase inhibition (IC50 = 4.52 μg/mL) compared to HRE. LCE fraction was also found to be non-toxic in the cell lines. After 6 weeks of administering 250 mg/kg bw of LCE, blood glucose levels significantly decreased, insulin response improved, and glycogen was partially restored in the liver and muscles. Histological findings indicated β-cell regeneration and protected liver architecture in treated hyperglycemic mice. Six bioactive compounds were identified, adhering to the Lipinski rule of five, and exhibiting potential antidiabetic activity. In silico findings showed these compounds bind to α-glucosidase and PPAR-γ receptors via hydrogen and hydrophobic interactions. Among the findings, rhodomyrtoxin, genistein, 8-methyl, cis-9-palmitoleic acid and sappanone A dimethyl ether demonstrated the best antidiabetic effects against α-glucosidase inhibition and PPAR-γ activation, indicating their potential as antidiabetic inhibitors. Based on these scientific findings, LCE may be a safe and potent antidiabetic inhibitor, offering an alternative herbal medicine for the future.